Institutional Mechanisms of Supporting Historical Memory in the Conditions of New Uzbekistan - Nabiyev Farruh (Indonesian Journal Publisher, 2025)
This article analyzes the institutional mechanisms that serve to strengthen the historical memory of society and its sustainable development in the conditions of New Uzbekistan. In the era of globalization, a sharp increase in information flows and increased cultural competition, the role of historical memory in social stability, awareness of national identity and spiritual development requires special attention. The article studies the functions of state administration bodies, the education system, the media, cultural and educational institutions, public organizations and scientific research centers in supporting historical memory. It also considers the reforms being implemented within the framework of the national idea and spiritual policy, new means of preserving and promoting historical heritage in the process of digitization. At the end of the study, proposals and conclusions are made aimed at increasing the effectiveness of historical memory institutions in New Uzbekistan.